Inside and beyond the Russo Ukrainian war: the pitfalls for the European Union - Marsili, M. (Newsletter Annual of the Academy of Yuste: Reflections on Europe and Ibero-America, 2023)
The Russo-Ukrainian conflict shows the limits and weaknesses of the European Union. More than this, the conflict reveals the inconsistencies between the EU principles and the policies implemented by the Union. Is not only the self-proclaimed role of the “global actor” that the EU imposed itself, that is questioned, but also the role of advocate of fundamental human rights that the Union claims to defend. Finally, the conflict warns of the risks of a hasty EU accession of Ukraine.